Ship graffiti on the East Adriatic coast - Praničević Borovac, Ita (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
On the insular and coastal area of Dalmatia about thirty sites with ship graffiti from Antiquity to the end of the 19th century have been found. Three quarters of the graffiti are found on sacral edifices, with a lesser number found on profane buildings or on rocks above the sea. Particularly valuable are ship drawings from earlier centuries, that, due to the lack of other information from that period, present valuable visual data about historic vessels, providing insight into the daily life and the rational world of the earlier inhabitants of this part of the Mediterranean.